THE EFFECT OF INVESTMENT MOTIVATION, PERCEIVED RISK AND FINANCIAL LITERACY ON INVESTMENT INTENTION - Kurniawati, Merry; Pamungkas, Ary Satria (International Journal of Application on Economics and Business, 2023)
Single investors in the capital market are only 2.73% of the total population of Indonesia. This means that there are still many Indonesians who have not invested, which can be caused by a lack of investment intention. Generation Z in West Kalimantan is still small, and one of the reasons is the attitude, behavior, and consumptive lifestyle of Generation Z, which has an impact on their intention in investing. This study was to determine whether there is an effect of Investment Motivation, Perceived Risk and Financial Literacy on Investment Intention. The research design used in this study is a descriptive research design with a quantitative approach. The sample in this study were generation Z (born 1997-2012), domiciled in West Kalimantan, have an intention in investing in the capital market but have never invested before. The number of samples used in this study were 347 respondents who were selected using a purposive sampling technique. Data analysis was carried out using the Structural Equation Modeling technique. The results of this study show that there is a positive effect of Investment Motivation on Investment Intention, there is a positive effect of Perceived Risk on Investment Intention, and there is a positive effect of Financial Literacy on Investment Intention.